2020
DOI: 10.3390/ijerph17113983
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Nursing Managers: A Systematic Review and Meta-Analysis of Related Factors, Levels and Prevalence

Abstract: Burnout syndrome is a major problem in occupational health, which also affects nursing managers. The main aim was to analyze the level, prevalence and risk factors of burnout among nursing managers. A systematic review with meta-analysis was conducted. The databases used were Medline (Pubmed), PsycINFO, CINAHL, LILACS, Scielo and Scopus. The search equation was “burnout AND nurs* AND (health manager OR case managers)”. Nursing managers present high levels of emotional exhaustion and a high degree of depersonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
2
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 35 publications
6
43
2
12
Order By: Relevance
“…The multiple mediation analyses showed that EI had an indirect effect on performance through professional efficacy and exhaustion-variables which fully mediated the link between EI and WP. These findings match with previous works that show the mediator effect of burnout between personal resources and work outcomes [42,45,46,57]. In this way, high EI levels help workers reduce their fatigue and improve their professional efficacy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The multiple mediation analyses showed that EI had an indirect effect on performance through professional efficacy and exhaustion-variables which fully mediated the link between EI and WP. These findings match with previous works that show the mediator effect of burnout between personal resources and work outcomes [42,45,46,57]. In this way, high EI levels help workers reduce their fatigue and improve their professional efficacy.…”
Section: Discussionsupporting
confidence: 91%
“…Among all these variables, EI emerges as an important and useful feature to group these skills and understand how the effects of burnout can be reduced on individual outcomes at work [42]. Several researchers have found that EI can help reduce the negative effects of the workload, exhaustion, job dissatisfaction, and stress of workers [43][44][45], contributing to improved social relations, performance, teamwork, effective leadership, etc., which have a noteworthy impact on work outcomes [45,46].…”
Section: Burnout As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation
“…As P-E t in feminity was proved adding signi cant variance explanation to burnout, our research could provide an advanced and more speci ed explanation for usually identi ed higher burnout levels in woman [4,5]. For, if female employees have higher feminity scores than their male colleagues [32,60,62], in a work environment with perceived low feminity, this could result in elevated P-E t in feminity (a bigger difference in individual and environment score) in the group of women.…”
Section: Discussionmentioning
confidence: 67%
“…Proceeding research shows a tendency for higher stress and burnout levels as well as poorer psychological health scores for women compared to men [4,5]. In most studies stress coping strategies and health strains have been compared for female and male groups, also considering the gender congruency of the individuals and their work environment, e.g.…”
Section: Introductionmentioning
confidence: 99%